Basal but divergent: Clinical implications of differential coagulotoxicity in a clade of Asian vipers. (August 2019) - Debono, Jordan; Bos, Mettine H.A.; Coimbra, Francisco; Ge, Lilin; Frank, Nathaniel; Kwok, Hang Fai; Fry, Bryan G.
Abstract: Envenomations by Asian pitvipers can induce multiple clinical complications resulting from coagulopathic and neuropathic effects. While intense research has been undertaken for some species, functional coagulopathic effects have been neglected. As these species' venoms affect the blood coagulation cascade we investigated their effects upon the human clotting cascade using venoms of species from the Azemiops, Calloselasma, Deinagkistrodon and Hypnale genera. Calloselasma rhodostoma, Deinagkistrodon acutus, and Hypnale hypnale produced net anticoagulant effects through pseudo-procoagulant clotting of fibrinogen, resulting in weak, unstable, transient fibrin clots. Tropidolaemus wagleri was only weakly pseudo-procoagulant, clotting fibrinogen with only a negligible net anticoagulant effect. Azemiops feae and Tropidolaemus subannulatus did not affect clotting. This is the first study to examine in a phylogenetic context the coagulotoxic effects of related genera of basal Asiatic pit-vipers. The results reveal substantial variation between sister genera, providing crucial information about clinical effects and implications for antivenom cross-reactivity. Highlights: Significant diversification exists in the coagulotoxicity of Asian viper venoms. These variations are likely to produce differential clinical effects. These variations are likely to translate into poor antivenom cross-reactivity.